2014
DOI: 10.1155/2014/865394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Macular, Peripapillary Nerve Fiber Layer and Choroid Thickness Changes in Behçet’s Disease with Spectral-Domain OCT

Abstract: Purpose. To assess the macular, choroid, and peripapillary nerve fiber layer thickness (RNFL) in Behçet's disease (BD) patients with and without ocular involvement by means of optical coherence tomography (OCT) and compare these findings with healthy controls. Design. Eighty patients with BD and 40 healthy controls who were followed up at the Uveitis and Retina Clinic of the Kayseri Research and Education Hospital in Turkey were enrolled in this prospective study. Subjects and Controls. The patients with BD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
1
26
0
2
Order By: Relevance
“…OCT has been universally adopted as an essential tool in management and follow up of uveitis. [ 32 , 38 , 39 , 45 , 46 ] Many attempts have been made to examine retinal, vitreoretinal and choroidal features using this non-invasive modality. [ 9 , 14 , 15 , 17 ] EDI OCT has revolutionised the way to look at the characteristic features in choroid in patients with retinal diseases and uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…OCT has been universally adopted as an essential tool in management and follow up of uveitis. [ 32 , 38 , 39 , 45 , 46 ] Many attempts have been made to examine retinal, vitreoretinal and choroidal features using this non-invasive modality. [ 9 , 14 , 15 , 17 ] EDI OCT has revolutionised the way to look at the characteristic features in choroid in patients with retinal diseases and uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…The prior study by Mustafa et al showed that mean FRT was thinner in eyes with Behcet's disease than in eyes of healthy controls [ 17 ]. This finding referred to permanent retina structural loss in the foveal area which is consistent with our study and found that thin FRT correlates with poor visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior histologic and imaging studies using FA, ICGA, and OCT have demonstrated increased thickness and volume of the choroid in patients with BD, but these findings were obtained during periods of inflammation affecting the retinal vasculature and choroid or subsequent to previous inflammation. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Although the pathophysiology of BD is unknown, studies have shown increased diffuse and focal infiltration of proinflammatory cells such as CD4+ T cells and macrophages in the choroid, as well as antibody and complement deposition. 3 These changes are believed to result in increased permeability of the choroidal vessels, leading to increased leakage that would be apparent on ICGA imaging.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Although the primary site of ocular involvement is the retina, a few studies have reported choroidal abnormalities as well. 12 , 13 , 14 , 15 In addition, abnormal FA findings have been reported in patients with non-ocular BD. 19 The aim of the current study was to evaluate choroidal changes in patients who have clinically diagnosed BD without clinical ocular involvement.…”
Section: Introductionmentioning
confidence: 99%